Higher proteotoxic stress rather than mitochondrial damage is involved in higher neurotoxicity of bortezomib compared to carfilzomib - YILMAZ GÖLER, AYŞE MİNE; YILMAZ, BETÜL; ARĞA, KAZIM YALÇIN (ELSEVIER, 2020)
Proteasome inhibitors have great success for their therapeutic potential against hematologic malignancies. First generation proteasome inhibitor bortezomib induced peripheral neuropathy is considered as a limiting factor in chemotherapy and its second-generation counterpart carfilzomib is associated with lower rates of neurotoxicity. The mitochondrial toxicity (mitotoxicity) hypothesis arises from studies with animal models of bortezomib induced peripheral neuropathy. However, molecular mechanisms are not fully elucidated and the role of mitotoxicity in bortezomib and carfilzomib induced neurotoxicity has not been investigated comparatively. Herein, we characterized the neurotoxic effects of bortezomib and carfilzomib at the molecular level in human neuronal cells using LC-MS/MS analysis, flow cytometry, RT-qPCR, confocal microscopy and western blotting. We showed that bortezomib and carfilzomib affected the human neuronal proteome differently, and bortezomib caused higher proteotoxic stress via protein oxidation, protein K48-ubiquitination, heat shock protein expression up-regulation and reduction of mitochondria membrane potential. Bortezomib and carfilzomib did not affect the gene expression levels related to mitochondrial dynamics (optic atrophy 1; OPA1, mitofusin 1; MFN1, mitofusin 2; MFN2, fission 1; FIS1, dynamin-related protein 1; DRP1) and overall mitophagy rate whereas, PINK1/Parkin mediated mitophagy gene expressions were altered with both drugs. Bortezomib and carfilzomib caused downregulation of the contents of mitochondrial oxidative phosphorylation complexes, voltage-dependent anion channel 1 (VDAC1) and uncoupling protein 2 (UCP2) similarly. Our findings suggest that, both drugs induce mitotoxicity besides proteotoxic stress in human neuronal cells and the higher incidence of neurotoxicity with bortezomib than carfilzomib is not directly related to mitochondrial pathways.
Keywords: Bortezomib; Carfilzomib; Mitotoxicity; Neurotoxicity; Peripheral neuropathy; UBIQUITIN-PROTEASOME SYSTEM; INDUCED PERIPHERAL NEUROPATHY; PREVENTS NEURONAL DEATH; HEAT-SHOCK PROTEINS; OXIDATIVE STRESS; 26S PROTEASOME; DEGRADATION; MITOTOXICITY; INHIBITORS; MITOPHAGY